Shape-based sorting of agricultural produce using support vector machines in a MATLAB/SIMULINK environment - Kyaw M.M.; Ahmed S.K.; Md Sharrif Z.A. (2023)
The ability to sort agricultural produce automatically is very important. This paper addresses one way to identify agricultural produce based on their shape. The techniques used are based on support vector machines. The images of the produce are loaded into MATLAB and the features extracted using image processing techniques based on edge detection. These features are then input to a classifier; i.e., a support vector machine, for identification. A regular digital camera is used for acquiring the image, and all manipulations are performed in a MATLAB / SIMULINK environment. The results obtained are an improvement over a previous technique. 2009 IEEE.